IMPLEMENTATION OF THE DIGITAL CIVIL REGISTRATION APPLICATION PROGRAM (IKD) IN PUNGGING DISTRICT, MOJOKERTO - Fitria, Laili Nur; Sukmana, Hendra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study is to describe and analyze the implementation of the IKD (Digital Population Identity) application program in Pungging District, Mojokerto Regency. The main focus of this study is to explore the challenges faced in the implementation of the IKD application and its impact on the quality of public services in Pungging District. Method: This study uses a qualitative descriptive research method with data sources obtained from interviews, observations, and documentation. This study focuses on the implementation of the IKD application in Pungging District, Mojokerto Regency, and uses Edward III's theory on policy implementation which covers four indicators; communication, resources, disposition (implementer attitude), and bureaucratic structure. Results: The results of the study show that the IKD application program in Pungging District can be summarized with 4 indicators: Communication, the implementation of the program has been socialized to convey information in a clear and structured manner. Resources, still constrained by human resources and no budget. Disposition, the implementer is capable of overcoming and explaining matters related to the IKD application program. Bureaucratic structure, the bureaucratic structure in implementation has been carried out according to SOPs that are not convoluted. Novelty: This research makes a new contribution by highlighting the implementation of the IKD application at the sub-district level. The novelty centers on a comprehensive comprehension of local determinants that affect the successful implementation of technology in public services, along with strategies to address current challenges to enhance the future effectiveness of the IKD application program.